2012
DOI: 10.1029/2012pa002378
|View full text |Cite
|
Sign up to set email alerts
|

El Niño–Southern Oscillation extrema in the Holocene and Last Glacial Maximum

Abstract: [1] The El Niño-Southern Oscillation (ENSO) is the largest engine of interannual climate variability on the planet, yet its past behavior and potential for future change are poorly understood and vigorously contested. Reconstructions of past ENSO are indispensable for testing climate models tasked with predicting future ENSO activity in a warming world, but suitable geologic archives are scarce, especially for the last glacial period. Here we reconstruct mean climate and ENSO variability in the Holocene and La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
318
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(364 citation statements)
references
References 71 publications
29
318
4
1
Order By: Relevance
“…3a,g). Contrast between March and September solar insolation at the equator also closely follows the pattern of changes in ENSO variability 15 supporting the hypothesis by Clement et al 13 However, recent complex coupled general circulation experiments 16 questioned these results. The intermediate complexity model (that is, the Cane and Zebiak model) used in the study by Clement et al 13 requires prescribed, but poorly known, ENSO mean state and therefore could lead to potential modelling artefacts 16 .…”
Section: Discussionsupporting
confidence: 74%
“…3a,g). Contrast between March and September solar insolation at the equator also closely follows the pattern of changes in ENSO variability 15 supporting the hypothesis by Clement et al 13 However, recent complex coupled general circulation experiments 16 questioned these results. The intermediate complexity model (that is, the Cane and Zebiak model) used in the study by Clement et al 13 requires prescribed, but poorly known, ENSO mean state and therefore could lead to potential modelling artefacts 16 .…”
Section: Discussionsupporting
confidence: 74%
“…3), corroborating existing records of high oceanic productivity in the TEP from ∼7,000-5,000 cal yr BP (refs 19,20). Our findings are consistent with a persistent, La Niña-like state in the tropical Pacific during the mid-Holocene [19][20][21] .…”
Section: Hiatussupporting
confidence: 80%
“…3), corroborating existing records of high oceanic productivity in the TEP from ∼7,000-5,000 cal yr BP (refs 19,20). Our findings are consistent with a persistent, La Niña-like state in the tropical Pacific during the mid-Holocene [19][20][21] .Sea temperatures reconstructed from Sr/Ca reflect warming from ∼19 • C at ∼5,100 cal yr BP to ∼25.5 • C at ∼4,600 cal yr BP (Fig. 3a), which may be related to the decline in upwelling during that time (Fig.…”
supporting
confidence: 78%
“…These authors suggested that the d 18 O c range reflected reduced salinities in the upper water column from mixing with a proximate source of 18 O-depleted glacial meltwater. Such studies demonstrate that an additional dimension of hydrographic information can be recovered when a suite of individual foraminifer shells are analyzed (Billups and Spero, 1996;Ford et al, 2015;Koutavas et al, 2006;Koutavas and Joanides, 2012;Rustic et al, 2015).…”
Section: Introductionmentioning
confidence: 99%